Deployment of a dynamic penetrometer from manned submersibles for fine‐scale geomorphology studies. (25th October 2013) - Stark, Nina; Le Dantec, Nicolas; Corella, Juan Pablo; Barry, David Andrew; Lemmin, Ulrich; Girardclos, Stéphanie; Kopf, Achim
<x xml:space="preserve">Abstract</x> Dynamic penetrometers reveal information about seafloor strength, stratification, stability, and sediment remobilization. However, positioning is often limited to a range of meters making it difficult to target small‐scale geomorphologic features. Deployments from submersed vessels (manned or remotely operated) can extend the possibilities of in situ geotechnical surveying in areas of complex bathymetry. The lightweight dynamic penetrometer Nimrod was modified to enable its deployment from the MIR submersibles, and was deployed during two dives in the Rhône Delta and Vidy Bay (both Lake Geneva). In the Rhône Delta, five positions at the floor/levee complex of a submarine canyon were sampled with 1 m spacing, with good reproducibility of the results. In Vidy Bay, so‐called pillow‐hollow structures on the lake bottom with dimensions of about 50 cm were targeted. At both sites, the penetrometer was released from a height of about 1‐2 m above the lake bottom using the starboard robotic arm of the MIRs leading to impact velocities of 3 m s−1. The probe reached penetration depths of up to 80 cm with maximum decelerations of up to 2.9 g. Stratification in the deceleration versus penetration depth profiles hinted at recent sediment remobilization processes. Pressure transducer results of the probe were suitable to determine water depth, and estimate trends of excess pore pressure. This article describes the modification of the dynamic penetrometer Nimrod for deployments from the MIR submersibles, assesses the deployment performance, validates the results, and gives an outlook on the application of this technique and the results.